Application of wet compress with self-made moisturizing antipruritic lotion in the treatment of chronic eczema and related nursing management (自拟润肤止痒洗剂湿敷治疗慢性湿疹的护理体会) - LI Zhijia (李志家) (中西医结合护理)
Objective To observe the effect of wet compress with self-made moisturizing antipruritic lotion in the treatment of chronic eczema, and summarized nursing measures．Method Totally 40 cases of chronic eczema patients were recruited, and a self-control method taking self contrast with their left and right hemibody. The control group was given Chinese herbal medicine external application, and the observation group was additionally treated by wet compress with self-designed moisturizing antipruritic lotion based on the treatment of the control group. The duration of treatment lasted 2 weeks．Patients’ both sides were measured by Rash score and pruritus score．Results After treatment of 2 weeks, the overall response rate of the observation group was higher than that of the control group(85. 00% vs. 70. 00%, P＜0. 05). The Eczema Area and Severity Index (EASI) score in the observation group was lower than that of the control group (P＜0. 05). Conclusion Wet compress with self-designed moisturizing antipruritic lotion can improve the treatment effect of skin lesions in patients with chronic eczema. (目的 观察自拟润肤止痒洗剂湿敷治疗慢性湿疹的效果, 总结护理经验。方法 选取40例慢性湿疹患者为研究对象, 采用左右自身对照, 分别给予不同的护理干预措施。对照侧给予中药涂擦, 观察侧在对照组的基础上给予自拟润肤止痒洗剂湿敷。2周后观察慢性湿疹患者皮损表现及瘙痒症状等指标。结果 治疗2周后, 受试者观察侧护理总有效率85. 00%(34/40), 高于对照侧的70. 00%(28/40), 差异有统计学意义(P＜0. 05)。观察侧湿疹面积和严重指数(EASI)总分低于对照组, 差异有统计学意义(P＜0. 05)。结论 采用自拟润肤止痒洗剂湿敷护理慢性湿疹患者, 能提高皮损改善效果。)